L'Hopital's Rule Might Not Help Here

Calculus Level 5

lim x 0 ( 1 x 2 e x ( e x 1 ) 2 ) \lim_{x\to 0} \left(\dfrac{1}{x^2} - \dfrac{e^x}{(e^x-1)^2}\right)

Find the reciprocal of the above limit.


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Feb 16, 2016

lim x 0 ( 1 x 2 e x ( e x 1 ) 2 ) = lim x 0 ( 1 x 2 e x e 2 x 2 e x + 1 ) = lim x 0 ( 1 x 2 1 e x 2 + e x ) By Maclaurin series = lim x 0 ( 1 x 2 1 2 ( x 2 2 ! + x 4 4 ! + x 6 6 ! + . . . ) ) = lim x 0 2 ( x 2 2 ! + x 4 4 ! + x 6 6 ! + . . . ) x 2 2 x 2 ( x 2 2 ! + x 4 4 ! + x 6 6 ! + . . . ) = lim x 0 2 ( x 4 4 ! + x 6 6 ! + x 8 8 ! + . . . ) 2 ( x 4 2 ! + x 6 4 ! + x 8 8 ! + . . . ) = lim x 0 1 4 ! + x 2 6 ! + x 4 8 ! + . . . 1 2 ! + x 2 4 ! + x 4 8 ! + . . . = 1 4 ! 1 2 ! = 2 ! 4 ! = 1 12 \begin{aligned} \lim_{x \to 0} \left(\frac{1}{x^2} - \frac{e^x}{(e^x-1)^2}\right) & = \lim_{x \to 0} \left(\frac{1}{x^2} - \frac{e^x}{e^{2x} -2e^x +1}\right) \\ & = \lim_{x \to 0} \left(\frac{1}{x^2} - \frac{1}{\color{#3D99F6}{e^x -2 + e^{-x}}}\right) \quad \quad \small \color{#3D99F6}{\text{By Maclaurin series}} \\ & = \lim_{x \to 0} \left(\frac{1}{x^2} - \frac{1}{\color{#3D99F6}{2\left(\frac{x^2}{2!}+\frac{x^4}{4!}+\frac{x^6}{6!}+...\right)}} \right) \\ & = \lim_{x \to 0} \frac{2\left(\frac{x^2}{2!}+\frac{x^4}{4!}+\frac{x^6}{6!}+... \right)- x^2}{2x^2\left(\frac{x^2}{2!}+\frac{x^4}{4!}+\frac{x^6}{6!}+...\right)} \\ & = \lim_{x \to 0} \frac{2\left(\frac{x^4}{4!}+\frac{x^6}{6!}+\frac{x^8}{8!}+... \right)}{2\left(\frac{x^4}{2!}+\frac{x^6}{4!}+\frac{x^8}{8!}+...\right)} \\ & = \lim_{x \to 0} \frac{\frac{1}{4!}+\frac{x^2}{6!}+\frac{x^4}{8!}+... }{\frac{1}{2!}+\frac{x^2}{4!}+\frac{x^4}{8!}+...} \\ & = \frac{\frac{1}{4!}}{\frac{1}{2!}} = \frac{2!}{4!} = \frac{1}{\boxed{12}} \end{aligned}

Interesting approach! You made one mistake though: the Maclaurin series of e x 2 + e x e^x - 2 + e^{-x} is 2 ( x 2 2 ! + x 4 4 ! + x 6 6 ! + . . . ) 2\left(\frac{x^2}{2!}+\frac{x^4}{4!}+\frac{x^6}{6!}+...\right) . So actually, the step before you use L'Hopital's rule would look like this: lim x 0 2 ( x 4 4 ! + x 6 6 ! + . . . ) 2 ( x 4 2 ! + x 6 4 ! + . . . ) \lim_{x\to 0} \dfrac{2\left(\frac{x^4}{4!}+\frac{x^6}{6!}+...\right)}{2\left(\frac{x^4}{2!}+\frac{x^6}{4!}+...\right)} Looks like you don't even need L'Hopital's rule in this case!

Ariel Gershon - 5 years, 3 months ago

Log in to reply

Thanks. I will amend the solution. Nice problem.

Chew-Seong Cheong - 5 years, 3 months ago

So finally a question to which you couldn't (and didn't) apply L'Hopital's Rule.

Anyway, exceptionally brilliant solution as always. Cheers! (+1)

Arkajyoti Banerjee - 4 years, 4 months ago

Elegent approach and I really love doing with this.

Naren Bhandari - 3 years, 8 months ago

=limx>0 e 2 x + 1 2 e x e x x 2 x 2 ( e x 1 ) 2 \frac{e^{2x}+1-2e^{x}-e^{x}*x^{2}}{x^{2}(e^{x}-1)^{2}} =limx>0 e 2 x + 1 2 e x e x x 2 x 4 ( e x 1 ) 2 x 2 \frac{e^{2x}+1-2e^{x}-e^{x}*x^{2}}{x^{4}\frac{(e^{x}-1)^{2}}{x^{2}}} =limx>0 e 2 x + 1 2 e x e x x 2 x 4 \frac{e^{2x}+1-2e^{x}-e^{x}*x^{2}}{x^{4}} Now if the limit has to exist we can just find the coefficient of x 4 x^{4} in numerator by applying the expansion of e. = 1 + 2 x + 4 x 2 2 ! + 8 x 3 3 ! + 16 x 4 4 ! . . . + 1 2 2 x 2 x 2 2 ! 2 x 3 3 ! 2 x 4 4 ! . . . . x 2 ( 1 + x + x 2 2 ! . . . ) 1+2x+\frac{4x^{2}}{2!}+\frac{8x^{3}}{3!}+\frac{16x^{4}}{4!}...+1-2-2x-\frac{2x^{2}}{2!}-\frac{2x^{3}}{3!}-\frac{2x^{4}}{4!}....-x^{2}(1+x+\frac{x^{2}}{2!}...) Taking out the coefficient of x 4 x^{4}

16 4 ! 2 4 ! 1 2 ! \frac{16}{4!}-\frac{2}{4!}-\frac{1}{2!} = 1 12 \frac{1}{12}

We can be sure that terms having power less than 4 will cancel out and more than 4 will become 0

the LaTeX code for the limit of a function f ( x ) f(x) is

\lim _{ x\rightarrow a }{ f(x) }

lim x a f ( x ) \lim _{ x\rightarrow a }{ f(x) } (what the math would look like)

or you can add \displaystyle so it'll look like this

lim x a f ( x ) \displaystyle\lim _{ x\rightarrow a }{ f(x) }

Hamza A - 5 years, 3 months ago

lim x 0 ( e x 1 ) 2 x 2 e x ( x ( e x 1 ) ) 2 \large \displaystyle \lim_{x \to 0} \frac{\left(e^x-1\right)^2-x^2e^x}{\left(x\left(e^x-1\right)\right)^2}

Plugging in e x = 1 + x + x 2 2 ! + x 3 3 ! + . . . e^x = 1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+... (Taylor's Expansion for e x e^x ):

= lim x 0 ( 1 + x + x 2 2 ! + x 3 3 ! + . . . 1 ) 2 x 2 ( 1 + x + x 2 2 ! + x 3 3 ! + . . . ) ( x ( 1 + x + x 2 2 ! + x 3 3 ! + . . . 1 ) ) 2 =\large \displaystyle \lim_{x \to 0} \frac{\left(1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+...-1\right)^2-x^2\left(1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)}{\left(x\left(1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+...-1\right)\right)^2}

= lim x 0 ( x + x 2 2 ! + x 3 3 ! + . . . ) 2 x 2 ( 1 + x + x 2 2 ! + x 3 3 ! + . . . ) ( x ( x + x 2 2 ! + x 3 3 ! + . . . ) ) 2 =\large \displaystyle \lim_{x \to 0} \frac{\left(x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)^2-x^2\left(1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)}{\left(x\left(x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)\right)^2}

= lim x 0 ( x + x 2 2 ! + x 3 3 ! + . . . ) ( x + x 2 2 ! + x 3 3 ! + . . . ) x 2 x 3 x 4 2 ! x 5 3 ! . . . ( x 2 + x 3 2 ! + x 4 3 ! + . . . ) 2 =\large \displaystyle \lim_{x \to 0} \frac{\left(x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)\left(x+\frac{x^2}{2!}+\frac{x^3}{3!}+...\right)-x^2-x^3-\frac{x^4}{2!}-\frac{x^5}{3!}-...}{\left(x^2+\frac{x^3}{2!}+\frac{x^4}{3!}+...\right)^2}

From here, it is pretty clear that the lowest powered term in the denominator will be x 4 x^4 . Evidently, for limit to exist and be non infinite, terms with a power lesser than 4 4 in the numerator must cancel out and the terms larger than 4 4 must equate to 0 0 as x 0 x \to 0 . Hence, we collect all the x 4 x^4 terms in the numerator to prepare for cancellation.

= lim x 0 ( x x 3 3 ! + x 2 2 ! x 2 2 ! + x 3 3 ! x x 4 2 ! ) x 4 =\large \displaystyle \lim_{x \to 0} \frac{\left(x\cdot \frac{x^3}{3!}+\frac{x^2}{2!}\cdot \frac{x^2}{2!}+\frac{x^3}{3!}\cdot x-\frac{x^4}{2!}\right)}{x^4}

= 1 6 + 1 4 + 1 6 1 2 = 1 12 =\frac{1}{6}+\frac{1}{4}+\frac{1}{6}-\frac{1}{2} = \boxed{\frac{1}{12}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...